Extraction and Applications of Grapefruit (Citrus paradise) Peel Oil Against E. coli - Imran, Kashaf; Saeed, Muhammad; Randhawa, Muhammad Atif; Sharif, Hafiz Rizwan (Pakistan Journal of Nutrition, 2013)
Phytochemicals has got special attention of researchers because of their value in food preservation and value addition due to consumer preference. Grapefruit (Citrus paradisi) is one of important member of family Rutaceae (citrus family). Oil was extracted through solvent extraction method using soxhlet’s apparatus. The nuggets were prepared by incorporating the grapefruit peel oil at different levels 0 (control), 5, 10, 25, 50, 100% and stored for duration period (0, 7 and 14 days). Peel oil refractive index, specific gravity, pH, acid value, iodine values 1.47, 0.85, 3.67, 0.81, 99.4 were respectively calculated. The peak values for proximate analysis (protein, moisture, fat, ash contents) were 62.32, 15.29, 14.0 and 2.76 respectively were recorded in T1 (5% grapefruit peel oil) at all storage periods. In color, water activity and texture analysis were 117.77, 0.94 and 1691.7 respectively in T1 at all storage durations. Similarly in sensory evaluation of color, taste, flavor and overall acceptability found statistically that T3 (25% grapefruit oil) treatment is highly significant at all storage periods and gave maximum value for these parameters and T5 (100% grapefruit oil) gave minimum value for its effectiveness. Grapefruit peel oil was checked for its antimicrobial activity test e.g., total plate count, disc diffusion method and minimum inhibitory action against Escherichia coli on chicken nuggets. In antimicrobial analysis MIC (Minimum Inhibitory Concentration) decreased with increasing the concentration of grapefruit peel oil and in disc diffusion method, its values increased with increasing grapefruit peel oil.